Comments on the taxonomic status of Neuquensaurus robustus (Huene) (Sauropoda, Titanosauria) - Otero, Alejandro (2010)
Neuquensaurus ("itanosaurus") is one of the best preserved sauropods from the Upper Cretaceous of Patagonia, which currently includes two species: Neuquensaurus australis (Lydekker) and Neuquensaurus robustus (Huene). "Titanosaurus" robustus was recognized mainly from a subset of bones previously assigned but not described by Lydekker to "Titanosaurus" australis. Huene classified the limb bones of "Titanosaurus" without comparing the vertebral material of each species and used the name of "Titanosaurus" australis in an arbitrary way to identify the form possessing slender limb bones and creating for the remainder the species "T". robustus, without taking into account the fact that the type material of "T". australis consists of a series of caudal vertebrae. This study agrees with other authors in consider N. robustus as nomen dubium till further studies which also include the axial skeleton shed new light on the taxonomic status of the species. The present analysis is focused on the appendicular anatomy of N. robustus. Because of its disarticulated condition, the new discoveries on the last years, as well as the similarity with N. australis, a reassessment of all available appendicular material of those species is given here. Several elements originally described as referred to "T". robustus are here considered as belonging to N. australis, such as a sternal plate (MLP-CS 1295), humerus (MLP-CS 1019), and ilium (MLP-Av 2069). Likewise, many elements originally referred to "T". australis closely resemble the lectotype of "T". robustus, for example, an ulna (MLP-CS 2004), femur (MCS 9), tibia (MCS 6), and several radii (e.g., MLP-CS 1196). Finally, some elements previously referred to "T". australis or "T". robustus seem to pertain to a different species or even genus due to their differences and/or their fragmentary condition. That is the case of some scapulae (e.g., MLP-CS 1296), radii (e.g., MLP-CS 1167), metacarpal II (MLP-CS 1186), metacarpal III (MLP-CS 2003), metacarpal IV (MLP-CS 1187), ilia (e.g., MLP-CS 1056), and pubis (MLP-CS 1263). Such elements are tentatively considered here as cf. Neuquensaurus.